Trends in utilization of tramadol and other opioids in Denmark 2017–2023: A nationwide drug utilization study - Rasmussen, Lotte; Ernst, Martin Thomsen; Forberg, Solveig; Pottegård, Anton; Søndergaard, Jens; Sørensen, Anne Mette Skov (British journal of clinical pharmacology, 2025)
The use of tramadol and other opioids for pain management has been accompanied by a multitude of challenges and concerns worldwide. The use of tramadol saw a decline in Denmark during 2017–2019 accompanied by a slight increase in the use of morphine and oxycodone. Using the Danish National Prescription Registry and utilizing data until and including 2023, we aimed to provide updated data on the utilization patterns of tramadol and other opioids in Denmark. We found a 35% decline in the use of tramadol from 2017 to 2023 most likely due to media attention, regulatory actions, health campaigns and targeted education of physicians and patients by the Danish health authorities. This decline was accompanied by an increase in the number of new (+90%) and current users of morphine (+57%), which surpassed those of tramadol, oxycodone and other opioids in 2023.